AI and Machine Learning in Retail Pharmacy: Systematic Review of Related Literature - Donepudi, Praveen Kumar (ABC Journal of Advanced Research, 2018)
Artificial intelligence and machine learning are the future of every field. These can be applied in any field for better or efficient performance. Both these can be used in retail pharmacy as a solution to different problems. The machine learning prediction model can help in predicting the disease of patients and it can also be used to predict the medicine for the patient. AI systems can be used to automate the tasks that will help in saving time and also the tasks will be performed by using fewer resources.